2021
DOI: 10.3390/ma15010094
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Studies on CO2 Sequestration of Concrete Slurry Water Using Supercritical CO2

Abstract: To prevent drastic climate change due to global warming, it is necessary to transition to a carbon-neutral society by reducing greenhouse gas emissions in all industrial sectors. This study aims to prepare measures to reduce the greenhouse gas in the cement industry, which is a large source of greenhouse gas emissions. The research uses supercritical CO2 carbonation to develop a carbon utilization fixation technology that uses concrete slurry water generated via concrete production as a new CO2 fixation source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…During the determined reaction time, specimens were undergoing Lean Carbonation. Most studies on mineral carbonation based on supercritical CO 2 were conducted in the ranges of 30-50 • C and 80-100 bar [32]. Based on these conditions, in this study, the temperature and pressure conditions were set to 35 • C and 80 bar and 40 • C and 100 bar, close to the supercritical CO 2 critical point (31.1 • C and 73.8 bar); the carbonation depth was measured by varying the curing time from 1 to 5, 10, 30, and 60 min.…”
Section: Supercritical Co 2 Curing Conditionsmentioning
confidence: 99%
“…During the determined reaction time, specimens were undergoing Lean Carbonation. Most studies on mineral carbonation based on supercritical CO 2 were conducted in the ranges of 30-50 • C and 80-100 bar [32]. Based on these conditions, in this study, the temperature and pressure conditions were set to 35 • C and 80 bar and 40 • C and 100 bar, close to the supercritical CO 2 critical point (31.1 • C and 73.8 bar); the carbonation depth was measured by varying the curing time from 1 to 5, 10, 30, and 60 min.…”
Section: Supercritical Co 2 Curing Conditionsmentioning
confidence: 99%
“…Therefore, in a previous study [ 26 ], mineral carbonation by supercritical CO 2 was performed for CSW, in which the CSW ratio was adjusted to 5% at a set temperature (40 and 80 °C) and pressure (100 and 150 bars) conditions based on previous studies. It was confirmed that complete carbonation occurred within only 10 min at 40 °C and 100 bar.…”
Section: Introductionmentioning
confidence: 99%